Chronologic Changes and Correlates of Loop Diuretic Dose in Patients with Left Ventricular Assist Device. Issue 6 (November 2017) - Kido, Kazuhiko; George, Bennet; Charnigo, Richard J.; Macaulay, Tracy E.; Brouse, Sara D.; Guglin, Maya
Abstract : No study has systematically evaluated the prevalence and dosages of diuretic use for patients after left ventricular assist device (LVAD) implantation. The primary objective was to characterize chronologic change in prevalence and doses of loop diuretics after LVAD placement. The secondary objective was to identify correlates of actual doses of loop diuretics. We retrospectively reviewed medical records of adult patients with LVAD implantation at the University of Kentucky. Prevalence of diuretic use and furosemide equivalent dose were assessed before LVAD implantation and at seven time points thereafter: 1 week, 1 month, 3 months, 6 months, 1 year, 18 months, and 2 years. Correlation analyses and linear mixed modeling were used to identify correlates of diuretic dose before and after LVAD implantation. Eighty-two consecutive eligible patients were reviewed. The prevalence of loop diuretic use was 95% at baseline but significantly lower than that at all subsequent time points ( p < 0.048 for all). Nevertheless, more than half of patients on whom we had such follow-up data were on loop diuretics 2 years after LVAD implantation. Average furosemide equivalent dose was significantly lower at every time point after implantation compared with baseline ( p < 0.006 for all). Blood urine nitrogen (BUN) was the most robust predictor of dose after LVAD implant. The prevalence and average furosemide equivalent dose were significantly reduced after LVAD implantation, but the use of loop diuretic remained more than 50% for up to 2 years. Consistent association with BUN may indirectly indicate overuse of diuretics post-LVAD implant. Abstract : Supplemental Digital Content is available in the text.